THE EFFECTIVENESS OF PROBLEM-BASED LEARNING (PBL) IN CHEMISTRY ON STUDENTS’ CRITICAL THINKING SKILLS: A LITERATURE REVIEW ON ITS IMPLEMENTATION IN INDONESIAN HIGHER EDUCATION INSTITUTIONS - Aslan Aslan (CV. ADIBA AISHA AMIRA, 2026)
Critical thinking skills are a fundamental competence required of students in the 21st century, particularly in the study of chemistry, which is abstract in nature and requires a deep conceptual understanding. This study aims to analyse the effectiveness of Problem-Based Learning (PBL)-based chemistry education on students’ critical thinking skills at Indonesian universities through a systematic literature review. The results indicate that PBL has been proven to be effective in enhancing students’ critical thinking skills, with an average N-Gain score of 0.71 in the high category and a 31 per cent increase in cognitive learning outcomes. The PBL framework, comprising five stages (problem orientation, learning organisation, individual and group investigation, presentation of results, and process evaluation), provides a systematic learning structure to develop the six indicators of critical thinking according to Facione, namely interpretation, analysis, evaluation, inference, explanation, and self-regulation. The implementation of PBL in Indonesian higher education institutions faces challenges such as limited learning time, a heavy curriculum load, variations in lecturers’ competence, and a lack of supporting facilities. However, PBL still offers advantages in making chemistry learning more contextual, encouraging independent learning, and developing collaborative skills and problem-solving in real-world situations. This study recommends the development of more valid PBL-integrated chemistry teaching materials, the integration of digital technology into PBL implementation, and the need for lecturer training to optimise their role as facilitators in PBL-based chemistry learning.